Management of Spinal Muscular Atrophy in the Adult Population. Issue 5 (26th February 2022) - Rad, Nassim; Cai, Haibi; Weiss, Michael D.
Abstract: Spinal muscular atrophy (SMA) is a group of neurodegenerative disorders resulting from the loss of spinal motor neurons. 95% of patients share a pathogenic mechanism of loss of survival motor neuron (SMN) 1 protein expression due to homozygous deletions or other mutations of the SMN1 gene, with the different phenotypes influenced by variable copy numbers of the SMN2 gene. Advances in supportive care, disease modifying treatment and novel gene therapies have led to an increase in the prevalence of SMA, with a third of SMA patients now represented by adults. Despite the growing number of adult patients, consensus on the management of SMA has focused primarily on the pediatric population. As the disease burden is vastly different in adult SMA, an approach to treatment must be tailored to their unique needs. This review will focus on the management of the adult SMA patient as they age and will discuss proper transition of care from a pediatric to adult center, including the need for continued monitoring for osteoporosis, scoliosis, malnutrition, and declining mobility and functioning. As in the pediatric population, multidisciplinary care remains the best approach to the management of adult SMA. Novel and emerging therapies such as nusinersen and risdiplam provide hope for these patients, though these medications are of uncertain efficacy in this population and require additional study.